Light chain deposition disease presenting with hepatomegaly: an association with amyloid-like fibrils. Issue 756 (October 1988) - Pelletier, G.; Fabre, M.; Attali, P.; Ladouch-Badre, A.; Ink, O.; Martin, E.; Etienne, J. P.
Abstract : We report an unusual case of lambda light chain deposits without overt plasma cell dyscrasia. The clinical presentation was hepatomegaly without biochemical sign of renal involvement. Portal hypertension, spontaneous rupture of the spleen and fracture of the 12th thoracic vertebra occurred during the course of the disease. Ultrastructural studies showed that lambda light chain deposits were associated with amyloid-like deposits. This case suggests that light chain deposition disease and amyloidosis could be two expressions of the same disease.